Subjective well-being among street mothers community - Fatwa Tentama; Nina Zulida Situmorang; Fitrianur Fitrianur (International Journal of Public Health Science (IJPHS), 2021)
The goal of this research was to understand the subjective well-being of mothers who work in the streets. This qualitative phenomenological study collected data using a semi-structured interview. Data were collected from six street mothers aged 18-40 years living in the dense residence of Kali Code, Karanganyar, Brontokusuman, Mergangsan, and Yogyakarta, Indonesia. The content analysis was used in this research, and the results showed that street mothers were satisfied with their current lives. Some of the reasons for their satisfaction include having a place to stay, gathering with their family every day, having a job, having independent earning, supporting children's education, and meeting their family's needs. This study also found that life satisfaction was associated with feeling satisfied with the self, family life, health, job, and community environment. Furthermore, participants expressed positive affect in the form of happiness when their job and earnings were good when gathering with the family or neighbors when the family is in harmony. The children are obedient when they can meet the needs of the children when they receive unexpected rewards. In contrast, the participants experienced negative affect in the form of guilt when they were unable to make the family happy, and disappointed when daily earnings were small. They were sad when children were not obedient, angry, and disappointed about living conditions and worried, anxious, and afraid about the workplace conditions.